Ochrona gruntów rolnych i leśnych jako element zrównoważonego rozwoju terenów wiejskich i regionów w Polsce - Olszańska, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The aim of this paper is an analysis of the problems connected with withdrawal of some territories from usage as agrarian lands and woodlands and evaluating use of the financial resources from the Fund for Protection of Agrarian Areas in Poland between 1995 and 2005. Data for the period analyzed in the paper were provided by the Main Statistical Agency. The analysis of the changes in structure of expenses of the money from the Fund for Protection of Agrarian Areas shows that the decreasing part of the financial resources in the following years was being spent on recultivating land and improving its quality which ought to be the main objective of the Fund for Protection of Agrarian Areas and that those actions were taken just in some of the provinces. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 178-185